Development of dual-wavelength and pulsed fiber lasers based on thulium-doped fibers / Salam Mahdi Azooz - Azooz, Salam Mahdi (2015)
A growing interest on lasers operating in the eye-safe two micron spectral region especially on dual-wavelength and pulse operations for a variety of applications motivated this PhD work. The scope of this thesis focuses on the development of new fiber lasers, which incorporates Thulium fiber as either gain medium or saturable absorber. At first, all-fiber dual-wavelength 2 μm fiber lasers are demonstrated based on three simple approaches; spatial filtering effect, inline microfiber Mach Zehnder Interferometer (MMZI) and multimode interference effect. The use of MMZI in the 2 μm laser cavity, for instance, successfully generates two simultaneous laser lines at 1952.93 and 1956.68 nm with a signal to noise ratio of more than 35 dB by using a cascaded commercial Thulium-doped fiber (TDF) and laboratory made double-clad Thulium-Ytterbium co-doped fiber (TYDF) as the gain media. Then, various Q-switched and mode-locked fiber lasers operating in 2 μm region were demonstrated using either the TDF or TYDF as the gain medium. Q-switched fiber lasers operating at 1949.0 nm and 1846.4 nm are successfully demonstrated based on nonlinear polarization rotation (NPR) technique and multi-walled carbon nanotubes (MWCNTs) saturable absorber (SA), respectively. A mode-locked fiber laser is also demonstrated by using a TYDF as the gain medium and commercial graphene oxide (GO) paper as SA. The mode-locked TYDFL has a repetition rate of 22.32 MHz and the calculated pulse width of 1.1 ns. Besides amplification purpose, a Thulium fiber can also be used as a SA in Erbium-doped fiber laser (EDFL) setups for both Q-switching and mode-locking applications. A dual-wavelength Q-switched EDFL EDFL operating at 1551.64 nm and 1534.8 nm was also demonstrated using the solid state TDF as the SA.